Dolphin bounty hunting in the history of the Italian fishery - Bavestrello, Giorgio; Cattaneo-Vietti, Riccardo; Meliada, Eleonora; Gnone, Guido (J. Cetacean Res. Manage., 2020)
In the Mediterranean, at the end of the 19thcentury, dolphins were identified as pest species for their disruptive actions during some fishing phases. Numerous fishermen organizations asked for permission to hunt dolphins, and the killing of a dolphin was often institutionally favoured by several national laws. We provide a picture of the systematic culling campaigns for dolphins in Italy up to the absolute prohibition of capture, analysing the governmental measures implemented against dolphins, the official number of individuals killed and their value (in Italian liras) in 11 Italian Maritime Compartments from 1927 to 1937. Officially, over 6,700 dolphins were killed in 10 years along the Italian coast and rewards distributed for about 360,160 Italian liras, which, at the current exchange rate, correspond to 355,000 euros, for a contribute of about 52 euros for each dolphin. Considering that the meat was consumed both at the family level or sold, mainly as salted and dried meat, the dolphin hunting could be considered a profitable activity in those years for the fishermen. Due to the scarce information available on the size of the dolphin populations around the Italian coast, it is difficult to estimate the impact of the bounty fishing on the Italian populations during the studied period. Nevertheless,it is possible to hypothesizethat it could have affected all the local recruitment, producing an effect on the local population far from being negligible.